Alamgeer Akhuwat - Zakir Naik, Dr. (Lahore Beacon Books, 2007)
The author is the President of Islamic Research Foundation and a populist international orator on Islam and comparative religion, acclaimed worldwide for his presentation, understanding and clarification of Islam, as well as removing misconceptions about Islam, specially amongst English audiences
Keywords: Brotherliness--Religious aspects--Islam -- Islam--Unity -- Occultism